CD 10: A Novel Stromal Marker in Pathogenesis and Prognosis of Invasive Breast Carcinoma - Jawahar, Devi; Arunagirinathan, Muruganantham; Murali, Induja (Annals of Pathology and Laboratory Medicine, 2020)
BACKGROUND: Breast carcinoma is the major cause of mortality and morbidity in Indian women. Though breast carcinoma arises from epithelial cells, stroma also plays a very important role in the pathogenesis of carcinoma breast which is assessed by the stromal marker CD 10. AIM : To study the stromal expression of CD 10 in carcinoma breast and find its relationship with other prognostic markers and study the role of stroma in pathogenesis of breast carcinoma. MATERIALS AND METHODS: 50 cases of breast cancer were included in the study. H & E slides were retrieved, reviewed and IHC was done with a panel of markers which included ER, PR, HER2/neu and CD 10. Stromal expression of CD 10 in invasive breast carcinoma was noted and analysed in correlation with other prognostic markers. RESULTS: Significances in the stromal CD 10 expression was calculated in regard to ER, PR & HER2/neu. Higher the tumour grade, more was the CD 10 stromal expression. CONCLUSION: As per the study, it is mandatory to include CD 10 stromal marker along with the panel of epithelial markers in invasive breast carcinoma. CD 10 contributes a potential target for development of novel therapies.